-5(9-11x)+8x-10=9x-12

Simple and best practice solution for -5(9-11x)+8x-10=9x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(9-11x)+8x-10=9x-12 equation:


Simplifying
-5(9 + -11x) + 8x + -10 = 9x + -12
(9 * -5 + -11x * -5) + 8x + -10 = 9x + -12
(-45 + 55x) + 8x + -10 = 9x + -12

Reorder the terms:
-45 + -10 + 55x + 8x = 9x + -12

Combine like terms: -45 + -10 = -55
-55 + 55x + 8x = 9x + -12

Combine like terms: 55x + 8x = 63x
-55 + 63x = 9x + -12

Reorder the terms:
-55 + 63x = -12 + 9x

Solving
-55 + 63x = -12 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-55 + 63x + -9x = -12 + 9x + -9x

Combine like terms: 63x + -9x = 54x
-55 + 54x = -12 + 9x + -9x

Combine like terms: 9x + -9x = 0
-55 + 54x = -12 + 0
-55 + 54x = -12

Add '55' to each side of the equation.
-55 + 55 + 54x = -12 + 55

Combine like terms: -55 + 55 = 0
0 + 54x = -12 + 55
54x = -12 + 55

Combine like terms: -12 + 55 = 43
54x = 43

Divide each side by '54'.
x = 0.7962962963

Simplifying
x = 0.7962962963

See similar equations:

| m=4-(-2)/-2-(-4) | | -2-c=(-1) | | 16m-4s+7m-6s= | | 9x^2+6x+3x=72-2+13x | | -8x-6+2w=-2+w | | 5p+10+4p=-35 | | x=x/2+x/3-2 | | x/-8=17(-5) | | (x+3)(x+3)=5 | | -12(x+3)+x+15=4-13x | | 7log(2x-20)=14 | | 16m-4m+7m-6s= | | 7x-(2x+4)=2x+(x-3)+3 | | 0,4+5=0,6z+0,6 | | 11p+13-8p=-17 | | 12/11 | | .25x=0 | | 36=r/6 | | -33=-36-6x+6 | | 9x^2+3x-5= | | -3.2x=-52.36 | | -33=-3x-6x | | 75-37= | | -8+2(3x+5)=-5+(x-4)+8x | | X+85+40=180 | | 3.2x=-52.36 | | 4(9+5m)-7m= | | g/200=0.011 | | -6=a/-4 | | 12y-4=9y+7 | | 2x+6=9-x | | 12y-4=9y |

Equations solver categories